Financing modes, risk, efficiency and profitability in Islamic banks: modeling for the GCC countries - Samir Belkhaoui; Naif Alsagr; Stefan van Hemmen (Cogent Economics & Finance, 2020)
The aim of this research is to develop a conceptual model that includes variables related to financing modes, risk-taking, efficiency, and Islamic bank profitability in GCC Countries. The results indicate that the total effect of financing modes on banks' profitability is high and statistically significant. The results show that a higher- level of participation in Mudharabah and Musharakah financing will generate high credit risk. Murabahah financing increases, directly and indirectly, the profitability and improve simultaneously the capitalization ratio and the cost efficiency for Islamic banks in the GCC countries. The contribution of our research is on two levels. On the one hand, our study is an addition to the literature that examined the determinants of Islamic banks performance. The conceptual model added risk-taking and cost efficiency as intervening variables in the profit-financing modes relationship. On the other hand, this research uses path analysis method, called second-generation approach, to test the model.
Keywords: G21; G32; O53; 330; Financing modes; risk; efficiency; profitability; islamic bank; path analysis; GCC countries